2-Cyanoisonicotinamide Conjugation: A Facile Approach to Generate Potent Peptide Inhibitors of the Zika Virus Protease - Patil, Nitin A. (2021)
The rapid generation and modification of macrocyclic peptides in medicinal chemistry is an ever-growing area that can present various synthetic challenges. The reaction between N-terminal cysteine and 2-cyanoisonicotinamide is a new biocompatible click reaction that allows rapid access to macrocyclic peptides. Importantly, 2-cyanoisonicotinamide can be attached to different linkers directly during solid-phase peptide synthesis. The synthesis involves only commercially available precursors, allowing for a fully automated process. We demonstrate the approach for four cyclic peptide ligands of the Zika virus protease NS2B-NS3. Although all peptides display the substrate recognition motif, the activity strongly depends on the linker length, with the shortest cyclization linker corresponding to highest activity (Ki = 0.64 μM). The most active cyclic peptide displays affinity 78 times higher than that of its linear analogue. We solved a crystal structure of the proteolytically cleaved ligand and synthesized it by applying the presented chemistry to peptide ligation.